PEMBUATAN PISANG COKLAT (PISCOT) / GAE COKOLA DESA SISABAMBOWO KECAMATAN ARAMO - Jhon Jhon Firman Fau (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Indonesia is one of the primary banana-producing countries, where there are currently more than 200 types of banana in Indonesia. The banana plant is a fertile and potential plant on the island of Nias, especially in Sisobambowo village in supporting the household economy. The development of the banana snack business in the household industry has developed in line with the availability of sufficient raw materials and very low industrial costs. Banana fruit is very suitable for increasing household economic growth because apart from household consumption, the banana commodity is very easy to obtain and can be done by anyone, including housewives. Sisobambowo villagers cannot take advantage of the potential of bananas to support the household economy. The benefit of this training is that the residents of Sisabambowo village can become entrepreneurs by using the existing potential, namely bananas.